Short-Term Response of Cytosolic NO3− to Inorganic Carbon Increase in Posidonia oceanica Leaf Cells - Rubio, Lourdes; García-Pérez, Delia; Davies, Julia M.; Fernández, José A. (Frontiers in Plant Science, 2020)
The concentration of CO2 in the atmosphere has increased over the past 200 years, and is expected to continue rising in the next 50 years at a rate of 3 ppm·year-1. This increase has led to a decrease in seawater pH that has changed inorganic carbon chemical speciation, increasing the dissolved HCO3-. Posidonia oceanica is a marine angiosperm that uses HCO3- as an inorganic carbon source for photosynthesis. An important side effect of the direct uptake of HCO3- is the diminution of cytosolic Cl- (Cl-c) in mesophyll leaf cells due to the efflux through anion channels and, probably, to intracellular compartmentalization. Since anion channels are also permeable to NO3- we hypothesize that high HCO3-, or even CO2, would also promote a decrease of cytosolic NO3- (NO3-c). In this work we have used NO3-- and Cl--selective microelectrodes for the continuous monitoring of the cytosolic concentration of both anions in P. oceanica leaf cells. Under light conditions, mesophyll leaf cells showed a NO3-c of 5.7±0.2 mM, which rose up to 7.2±0.6 mM after 30 min in the dark. The enrichment of natural seawater (NSW) with 3 mM NaHCO3 caused both a NO3-c decrease of 1±0.04 mM and a Cl-c decrease of 3.5±0.1 mM. The saturation of NSW with 1000 ppm CO2 also produced a diminution of the NO3-c, but lower (0.4±0.07 mM). These results indicate that the rise of dissolved inorganic carbon (HCO3- or CO2) in NSW would have an effect on the cytosolic anion homeostasis mechanisms in P. oceanica leaf cells. In the presence of 0.1 mM ethoxyzolamide, the plasma membrane-permeable carbonic anhydrase inhibitor, the CO2-induced cytosolic NO3- diminution was much lower (0.1±0.08 mM), pointing to HCO3- as the inorganic carbon species that causes the cytosolic NO3- leak. The incubation of P. oceanica leaf pieces in 3 mM HCO3--enriched NSW triggered a short-term external NO3- net concentration increase consistent with the NO3-c leak. As a consequence, the cytosolic NO3- diminution induced in high inorganic carbon could result in both the decrease of metabolic N flux and the concomitant biomass N impoverishment in P. oceanica and, probably, in other aquatic plants.